Teachers' perceptions on their actual teaching performances: a case study of English preparatory school teachers' perceptions in Eastern Mediterranean University of North Cyprus - Sonyel, B. (2010)
This research is carried out to explore teachers’ perspectives upon their teaching practices with respect to the in-service training program, C.O.T.E. they had been through. Teaching and in-service training have always been my interest area. Besides, after having informal conversations with the administrators from the Ministry of Education and owing to my observations, in North Cyprus the current education system needs to reformed considering main themes such as curriculum, in-service, pre-service training, material and curriculum design, lifelong learning, duration of school hours, financial issues and so forth.